Impact of COVID-19 restrictions on health and well-being in the United Arab Emirates - Dalibalta, Sarah; Ghader, Nariman; Rabah, Layal; Shaban, Sami; Al Mheiri, Noor (Frontiers in Psychology, 2023)
Background Restrictions during the COVID-19 pandemic are thought to have impacted both the physical health and well-being of individuals where lockdown was applied. The United Arab Emirates (UAE) was one of the leading countries in implementing the international guidelines to limit the intensely contagious nature of the outbreak. Aim To identify the impact of COVID-19 on changes to exercise and general physical activity habits, changes to the consumption of various foods and potential weight gain, as well as any differences in smoking habits among individuals residing in the UAE during the COVID-19 quarantine. Methods This is a cross-sectional analytical study that used a quantitative electronic questionnaire sent by the Ministry of Health and Prevention to individuals on its platform in order to collect data on the physical health and well-being of a UAE sample population. A total of 2,362 responses were received to specific questions on physical activity, eating habits, and tobacco use for the period before, during, and after the COVID-19 lockdown. Descriptive statistical analysis was used to display the sample’s demographic data and the changes in physical health and well-being. Paired t-test was used to show the changes in dietary habits. Results This study reveals concerning changes in health risk behaviors during the COVID-19 lockdown in the UAE. Physical activity levels declined across mild, moderate and vigorous ranges in most participants. Alarmingly, sedentary behavior dramatically increased with 71% of participants spending an average of 4–8 h per day sitting and over 54% of participants spending more than 4 h watching TV on an average day during lockdown. Fast-food consumption and snacking rose, hence weight gain was observed in over 53% of participants. Smoking habits, especially among cigarette smokers, may have worsened, with 45.2% reporting an increase in cigarette smoking, 16.8% declaring an increase in shisha smoking and 35.3% reporting an increase in smoking other tobacco products. These unfavorable behaviors during confinement could have serious long-term health consequences. Conclusion This study demonstrates that long periods of home quarantine may have led to unhealthy consequences that increase the risk of developing disease. This study therefore aims to highlight these health impacts, and recommend strategies and policies that can encourage healthy habits.